Study on Establishing the Basic Engaging Equation of Harmonic Drive By the B Metrix Method - 辛洪兵; 谢金瑞; 何惠阳 (Jixie chuandong)
The basic engaging equation of the Harmonic Drive is established by using the B metrix method Which is presented in the literature . The Harmonic Drive B Metrix is suitable for any wave Style. When we analysis the rigid gear tooth profiles conjugating with the spline with different gear profile, the B Metrix will not be changed.We find that there are two zones of action and two part of conjugate profiles on each side of spline tooth profile.